Playing the Believing Game with Dr. Seuss and Reluctant Learners in Science - Kym Buchanan; Perry Cook (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
Dr. Seuss’ Green Eggs and Ham offers insights for teachers trying to overcome learners’ reluctance.